Commodities Versus Stocks: Analysis of Their Performance from 2009 Through 2015 - Krawiec, Monika (European Journal of Multidisciplinary Studies, 2016)
Although over the last several years one could have witnessed unprecedented interest in commodity investments, the view of commodities from an investor’s perspective is of more recent date (with the exception of precious metals). There are several reasons for investing in commodities. First of all, they let investors gain equity-like or higher returns. Then, they can help to mitigate risk and improve portfolio diversification. They can also provide a possible hedge against unanticipated inflation. The growing popularity of commodity investing has been followed by a great number of new investment vehicles that make commodity investments available to a wider audience. Thus, investors based on their risk-return criteria and individual requirements may select from a broad range of commodity-linked financial instruments. One of possibilities is investing through a commodity index. This approach is especially attractive to investors that are familiar with investing in stock indexes. In theory, commodity indexes share a similar goal: to create a broad indicator of commodity price movements, though in practice portfolio weightings, construction, and calculation methodology vary significantly from one index to another. The most important of commodity indexes are: the Thomson Reuters/Core Commodity CRB Index, the S-P Goldman Sachs Commodity Index, the Bloomberg Commodity Index (former Dow-Jones AIG Commodity Index), and the Deutsche Bank Liquid Commodity Index. The present paper is aimed at assessing return and risk characteristics of these indexes and at providing a comparative analysis of their performance in relation to the most important equity indexes, such as S-P500, FTSE100, CAC40, DAX, WIG, BUX, IBovespa, Nikkei, Shanghai Composite (SSE), TSE300 (current S-P/TSX Composite Index), and AOI (All Ords). The empirical data covers daily quotations from January 5, 2009 to December 30, 2015. To verify whether the commodity indexes returns differ significantly from the returns of equity indexes, the nonparametric Mann-Whitney test is applied. The test has been chosen as returns of commodity indexes are not normally distributed.